2012
DOI: 10.1177/0022034512466265
|View full text |Cite
|
Sign up to set email alerts
|

Brain Activity and Human Unilateral Chewing

Abstract: Brain mechanisms underlying mastication have been studied in non-human mammals but less so in humans. We used functional magnetic resonance imaging (fMRI) to evaluate brain activity in humans during gum chewing. Chewing was associated with activations in the cerebellum, motor cortex and caudate, cingulate, and brainstem. We also divided the 25-second chew-blocks into 5 segments of equal 5-second durations and evaluated activations within and between each of the 5 segments. This analysis revealed activation clu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
38
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 28 publications
2
38
0
1
Order By: Relevance
“…In previous fMRI reports, in which isotonic muscle contraction was performed with gum-chewing and tooth-tapping tasks, much wider areas of activation were demonstrated in the cortex than in isometric contraction tasks. 13,21,22,24,29 Additionally, no major differences were observed in brain activity within low levels of tooth clenching with controlled force. 30 Quintero et al 24 investigated brain activity during gum-chewing task and found activation in the cerebellum, which is involved in the co-ordination and rhythmicity of oral functions as well as activity in the cortical and subcortical areas.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…In previous fMRI reports, in which isotonic muscle contraction was performed with gum-chewing and tooth-tapping tasks, much wider areas of activation were demonstrated in the cortex than in isometric contraction tasks. 13,21,22,24,29 Additionally, no major differences were observed in brain activity within low levels of tooth clenching with controlled force. 30 Quintero et al 24 investigated brain activity during gum-chewing task and found activation in the cerebellum, which is involved in the co-ordination and rhythmicity of oral functions as well as activity in the cortical and subcortical areas.…”
Section: Discussionmentioning
confidence: 88%
“…20 In first-step data analysis for each participant, we calculated BOLD signal changes between clenching and rest blocks and observed activation pattern in the cortical mastication area as described in previous studies (Figures 2 and 4). [21][22][23][24] Byrd et al 14 compared self-reporting patients with bruxism and the control group using fMRI. They found hypoactivation in the motor cortex (supplementary motor area, sensorymotor area and rolandic operculum) and the subcortical (caudate) areas in patients with bruxism in parafunctional movements.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have identified brain activation of the cerebellum and the motor cortex when participants were chewing (Onozuka et al, 2002; Quintero et al, 2013). In the current study, we further investigated the brain signatures associated with masticatory performance, a widely used index for evaluating the masticatory function of elderly people.…”
Section: Discussionmentioning
confidence: 99%
“…However, as a highly coordinated rhythmic and automatic movement, mastication is also regulated by the central nervous system (CNS; Avivi-Arber et al, 2011). Neuroimaging evidence has suggested that mastication is associated with the brain activity in the cortical sensory and motor regions, the subcortical regions, and the cerebellum (Onozuka et al, 2002; Quintero et al, 2013). Furthermore, in elderly healthy subjects, good masticatory ability, as indexed by higher masticatory performance, was associated with greater gray matter volume at the premotor cortex (PMC) and an increased resting-state functional connectivity (FC) with the cerebellum (Lin et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The investigators interpreted this to mean that somatosensory feedback via the vSI towards the motor cortex might play a particularly important role in the development of classical singing skills. Chewing, a more vital orofacial function, was also reported to activate the vSI bilaterally [7,8]. This suggests that chewing also requires information processing in the vSI to control or monitor a series of movements despite its semi-automatic nature.…”
Section: Introductionmentioning
confidence: 97%